PEDAGOGICAL DESIGN AND INNOVATIONS IN THE DESIGN-EDUCATIONAL SPACE - Romanenko, Natalia; Tarahtiy, Lesya (SWorldJournal, 2025)
IntroductionThe paper analyzes the use of pedagogical design as one of the areas of innovation in the design education space. Innovative implementations in the educational space of training masters of the specialty B2 (022) design at Cherkasy State Techn